Development of rainfall-runoff modelling using the HEC-HMS at the catchment of Kelantan River, Malaysia. Issue 1 (January 2021) - Armain, M Z S; Hassan, Z; Mohd Remy Rozainy, M A Z; Harun, S; Azam, N S; Mahyun, A W; Salwa, M Z M; Kamarudzaman, A N; Seman, N A
Abstract: The simulation of rainfall-runoff is important to be analysed at the Kelantan River catchment as flood is one of the common natural disasters in Kelantan. Sustainable water management in this region is only feasible following the availability of reliable information on the rainfall-runoff and other hydrological determinants that affect the water system. This study aims to evaluate the effects of extreme rainfall on the runoff at the catchment of the Kelantan River where recurrent floods have been occurring since 1988 to 2019. The study employs the remote sensing and geographic information system (GIS) integrated with the Hydrologic Engineering Center–Hydrologic Modelling Systems (HEC-HMS) to delineate the catchment line and simulate the river discharge. The observed discharge is used during the calibration and validation process to evaluate the performance of the integrated model. The model performed satisfactorily by obtained R 2 with the range of 0.80-0.97 and 0.64-0.93 in each sub-catchment during the calibration and validation period. The finding indicates that the developed HEC-HMS model has the ability to simulate event-based runoff.